Lifestyle, attitudes and needs of uncured XDR‐TB patients living in the communities of South Africa: a qualitative study. Issue 9 (18th May 2015) - Senthilingam, Meera; Pietersen, Elize; McNerney, Ruth; te Riele, Julian; Sedres, Pat; Wilson, Ruth; Dheda, Keertan
Summary Objective Patient‐level data are required to inform strategies interrupting transmission and default in patients with extensively drug‐resistant TB (XDR‐TB) to improve models of care and identify potential routes of transmission. We therefore explored the experiences, lifestyle, attitudes and needs of patients with uncured XDR‐TB, who failed or interrupted therapy, living without treatment in the community. Methods We conducted in‐depth interviews with 12 community‐based patients from South Africa. Family members were interviewed when patients were unavailable. Interviews were analysed using inductive thematic analysis. Results The thematic experiences identified from the interviews were as follows: (i) living with but not being cured of XDR‐TB, (ii) altered lifestyle in the community, (iii) experiences with community health care, (iv) local community members, and (v) wants and needs. Patients identified mistrust in health care, futility of treatment regimens, a need for a purpose in life and subsistence as major concerns. Restriction of living in the community for patients whose treatment had failed resulted in self‐imposed isolation. Defaulters focused more on the never‐ending drug regimen and bad experiences with health care contributing to non‐adherence. Family members emphasised an under‐recognised experience of unforeseen burden, obligation, worry and discomfort. Lack of knowledge and lack of concern about transmission was evident. Conclusion Current models of care are not adequately meeting the needs of patients with uncured XDR‐TB and relatives. These data inform the need for community‐based palliative care, vocational facilities to improve economic opportunities, home‐based infection control and improved psychosocial support to increase patient adherence, reduce transmission, provide income and relieve the burden on family members.